2022
DOI: 10.1177/11782234221080553
|View full text |Cite
|
Sign up to set email alerts
|

Combining Carbon-Ion Irradiation and PARP Inhibitor, Olaparib Efficiently Kills BRCA1-Mutated Triple-Negative Breast Cancer Cells

Abstract: Background: Triple-negative breast cancer (TNBC) exhibits poor prognosis due to the lack of targets for hormonal or antibody-based therapies, thereby leading to limited success in the treatment of this cancer subtype. Poly (ADP-ribose) polymerase 1 (PARP1) is a critical factor for DNA repair, and using PARP inhibitor (PARPi) is one of the promising treatments for BRCA-mutated (BRCA mut) tumors where homologous recombination repair is impaired due to BRCA1 mutation. Carbon ion (C-ion) radiotherapy effectively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…This study provides evidence that BUB1i increases the sensitivity of PARPi (olaparib) in BRCA mutant TNBC cells ( Figure 6 ). This effect was compounded when combined with radiation ( Figure 6 ), similar to what has been suggested by Kawanishi [ 52 ] and Feng [ 53 ] for BRCA mutant TNBC. Although recent studies have demonstrated that PARP inhibitor sensitivity does not depend on BRCA mutations [ 54 ], different cell lines have differential sensitivity/resistance to PARP inhibitors.…”
Section: Discussionsupporting
confidence: 82%
“…This study provides evidence that BUB1i increases the sensitivity of PARPi (olaparib) in BRCA mutant TNBC cells ( Figure 6 ). This effect was compounded when combined with radiation ( Figure 6 ), similar to what has been suggested by Kawanishi [ 52 ] and Feng [ 53 ] for BRCA mutant TNBC. Although recent studies have demonstrated that PARP inhibitor sensitivity does not depend on BRCA mutations [ 54 ], different cell lines have differential sensitivity/resistance to PARP inhibitors.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, we found that PARP inhibition does not affect cell killing by CIRT. Previous work showed that combining CIRT with the PARPi olaparib enhanced radiosensivity in the BRCA1-mutated triple-negative breast cancer cell line HCC1937, but had no effect on the BRCA wild-type cell line MDA-MB-231 35 . We postulate that PARP activity is not required for the response to CIRT-induced DNA damage unless the cell line is HR-defective.…”
Section: Discussionmentioning
confidence: 99%
“…Olaparib in combination with radiotherapy was well tolerated in TNBC [184] . Low-dose long-term treatment with olaparib may improve the radiosensitivity of TNBC [185] , and olaparib may be a promising radiosensitizer for TNBC [186] . Although the clinical benefit of olaparib can be observed in different types of TNBC, the pCR rate is higher in gBRCA carriers than in non-carriers, and BRCA mutation remains an important factor affecting the treatment and prognosis of TNBC [187] .…”
Section: Small Molecule Drugs Targeting Tnbcmentioning
confidence: 99%